DISCIPLINE ATTITUDE OF ELEMENTARY SCHOOL STUDENTS ON DISTANCE LEARNING - Hadi, Waluyo; Lestari, Ika; Nafiah, Maratun; Hidayah, Siti Nurul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The Covid-19 pandemic has hit Indonesia for about a year, and many activities have shifted online. No exception in the field of education. Learning is done online or in distance learning. The existence of distance learning does not rule out the possibility of bringing a change, including student discipline. This study has a purpose, namely to determine the field of elementary school students during distance learning. Descriptive quantitative is used as a method in conducting this research. Respondents in this study were 41 students at the State Elementary School 02 Pagelaran, Pemalang, Central Java. Filling out the questionnaire was used as a way to collect data. The results showed that at the time of distance learning, students' discipline was included in the moderate category with 46%, and the results could not be generalized to all elementary school levels in Indonesia.